Sharpening Intelligences by Developing Vocabularies Through Book Report - yustin sartika (Jurnal CULTURE (Culture, Language, and Literature Review), 2014)
All students will come into the classroom with different sets of developed intelligences. This means that each student will have his/her own unique set of intellectual strengths and weaknesses. These sets determine how easy or difficult it is for a student to learn information when it is presented in a particular manner. This is commonly referred to a learning style. Many learning styles can be found within one classroom. This article shows how teachers can teach book report more effectively through more interesting strategies. By developing vocabularies and using a mix of media or multimedia which is appropriate to learning style, it would not only about “Book Report”, the traditional listing of characters, settings, and plots.   Key words: intelligence, learning style, developing vocabulary, multimedia